Synthesis and characterization of glycolide, L-lactide, and PDMS-based terpolymers as a support for cell cultures - KAYAMAN APOHAN, NİLHAN (TAYLOR & FRANCIS LTD, 2002)
Poly(lactic acid)/poly(glycolic acid) /poly(dimethylsiloxane) (PLGA/TEGOMER) terpolymers have been synthesized by the ring-opening polymerization of L-lactide and glycolide with alpha, omega-amine-terminated poly(dimethylsiloxane) prepolymer, using stannous octoate as a catalyst. The resulting terpolymers were characterized by various analytical techniques including size exclusion chromatography, H-1-nuclear magnetic resonance (H-1-NMR), Fourier transform infrared spectroscopy, and differential scanning calorimetry. The data showed that the terpolymers presented an amorphous structure. The glass transition temperature decreased with increasing TEGOMER unit content. For in vitro degradation studies, porous films were fabricated using a solvent-casting, particulate leaching technique. Degradation of the PLGA/TEGOMER terpolymer was studied in phosphate-buffered saline at pH 7.4 and 37degreesC. The degradation was followed by intrinsic viscosity, mass loss, and molecular weight measurements, and H-1-NMR spectroscopy. The mass loss after 55 days was 76% for the PLGA/TEGOMER (71/24/5) sample. Cell growth experiments using Swiss 3T3 fibroblasts demonstrated that PLGA/TEGOMER terpolymer matrices allow the attachment and growth of cells.
Keywords: degradation; cell growths; poly(lactic acid); poly(glycolic acid); POLY(ETHYLENE GLYCOL); COPOLYMERS; DEGRADATION; ACID; TISSUE; TRANSPLANTATION; POLYMER; LIVER